INTEGRATION OF INFORMATION TECHNOLOGIES IN THE STUDY AND REHABILITATION OF RESPIRATORY MUSCLES - Habibulla Pulatov; Muhammad Mustafo Abduvohidov; Bahrom Khudoyberdiyev (Western European Studies, 2025)
The development of information technologies has significantly enhanced the possibilities for studying and rehabilitating the respiratory muscles. This paper explores the integration of digital tools, such as computer modeling, artificial intelligence (AI), and sensorbased monitoring systems, in assessing the morphology and function of respiratory muscles. Using biomechanical simulations and smart diagnostic devices, researchers can analyze muscle activity, breathing patterns, and performance under various physiological conditions. Furthermore, AI-assisted rehabilitation systems and virtual reality (VR) platforms provide personalized respiratory training programs for patients with pulmonary dysfunctions. The integration of IT not only improves diagnostic precision but also enhances treatment outcomes and accelerates recovery in respiratory medicine.
Keywords: Respiratory muscles; information technologies; artificial intelligence